6x + 4y = 12...subtract 6x from both sides
4y = -6x + 12 ...divide both sides by 4
(4/4)y = (-6/4)x + 12/4...reduce
y = -3/2x + 4 <== y = mx + b
When we simplify (3 + √5)(3 + √2), the result obtained is:
9 + 3√2 + 3√5 + √10
<h3>Surd operation </h3>
a√b × c√d = (a × c)√(b × d)
<h3>How to simplify (3 + √5)(3 + √2)</h3>
(3 + √5)(3 + √2)
Expand by clearing the bracket
3(3 + √2) + √5(3 + √2)
9 + 3√2 + 3√5 + √10
Thus,
(3 + √5)(3 + √2) = 9 + 3√2 + 3√5 + √10
Learn more about surd:
brainly.com/question/24700530
#SPJ1
15 cucumbers to 45 carrots...
so the ratio of cucumbers to carrots is : 15/45 which reduces to 1/3 <==
Answer:A
Step-by-step explanation:
If the auto insurance covers theft up to $15,000 and his car value is less than it ($8,000), he is going to pay only $250 deductible. It means that it covers values until $15,000.